2005
DOI: 10.1364/josaa.22.002613
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical definition and analysis of the Retinex algorithm

Abstract: We present a detailed mathematical analysis of the original Retinex algorithm due to Land and McCann [J. Opt. Soc. Am. 61, 1 (1071)]. To this end, we propose an analytic formula that describes the algorithm behavior. More than one Retinex version (e.g., with and without threshold) is examined. The behavior of Retinex varying the number of paths is predicted, and its recursive iterations are mathematically analyzed using the formula. The mathematical setting presented serves as a common ground for the various R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(136 citation statements)
references
References 22 publications
1
135
0
Order By: Relevance
“…In order to develop a generic model that can truthfully predict PDR, sensory and cognitive processes involved in extraction of this attribute from complex stimuli need to be taken into account. Previous research has shown that the area of the brightest patches and the image topology affect the perception of lightness and contrast [17,19,26], and therefore should be considered in constructing such a PDR model. Furthermore, image contrast and colorfulness are important factors in visual perception and, based on previous findings [8,11,24,25], could be involved in the process related to the extraction of observed image attributes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to develop a generic model that can truthfully predict PDR, sensory and cognitive processes involved in extraction of this attribute from complex stimuli need to be taken into account. Previous research has shown that the area of the brightest patches and the image topology affect the perception of lightness and contrast [17,19,26], and therefore should be considered in constructing such a PDR model. Furthermore, image contrast and colorfulness are important factors in visual perception and, based on previous findings [8,11,24,25], could be involved in the process related to the extraction of observed image attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the anchoring theories, the Retinex theory indirectly arrives to the same conclusion through a probabilistic formulation. This is achieved by averaging luminance values along paths of pixels originating from each point of the picture [19], while taking into account the relative distance between patches of different brightness.…”
Section: Perceived Lightnessmentioning
confidence: 99%
“…This is done on each chromatic channel separately. We briefly recall the mathematical description of retinex given in [35].…”
Section: A MI Retinexmentioning
confidence: 99%
“…On the other hand, Retinex-based methods are based on the human color perception system [10,11]. Provenzi et al mathematically analyzed the Retinex algorithm and demonstrated the performance according to various parameters such as threshold and the number of path of light paths to a pixel [11].…”
Section: Introductionmentioning
confidence: 99%
“…Provenzi et al mathematically analyzed the Retinex algorithm and demonstrated the performance according to various parameters such as threshold and the number of path of light paths to a pixel [11]. The Retinex methods enhance the input image by eliminating the illumination component using the low-pass filtering and logarithmic transformation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%